The Beneficial Effect of Two Nutraceuticals in Flea Allergy Dermatitis Itch Control: A Comparative Study - Cornegliani Luisa; Alice Guidi Eleonora; Persico Paola; Emidio Crisi Paolo; Pignataro Giulia; Belà Benedetta; Gramenzi Alessandro (International Journal of Nutrition, 2024)
This prospective randomized double-blinded multicentric study aimed to assess the efficacy of a new nutraceutical in controlling itch and skin lesions caused by flea allergy dermatitis (FAD) and compare it with another oral product of proven efficacy. Forty-three dogs, of different age, breed and sex, with FAD were included and divided into two groups: 24 received product A and 19 product B. Both groups received the same antiparasitic treatment. A modified canine atopic lesion index (mCADLI) and pruritus visual analogic scale (pVAS) were recorded at days 0, 30 and 60. pVAS was evaluated both by the examining veterinarian (vpVAS) and the owner (opVAS). Results obtained were compared between the two groups at each time point. In both groups of dogs, a significant decrease of mCADLI, vpVAS and opVAS at day 30 and 60, compared to day 0, was observed. At baseline, the mCADLI scores of Group B were significantly higher than Group A (95% CI: -4.0 to 0.0, p < 0.05), with no differences at D30 and D60 (not significant, p > 0.05). In Group B, significantly lower values of vpVAS were observed at D30 compared to Group A (95% CI: -2.5 to 0.0, p < 0.05), but not at D60 (not significant, p > 0.05). The median values of pVAS in Group B were lower compared to Group A at both D30 (95% CI: -2.5 to 0.4, p < 0.01) and D60 (95% CI: -3.0 to 0.3, p < 0.05). Both nutraceuticals can be useful to control discomfort, skin lesions and pruritus due to flea allergy dermatitis and can be a valuable replacement for antipruritic drugs antihistamines, steroids or Il-31 inhibitors.
Keywords: FAD